Use of two conventional staining methods to assess the acrosomal status of stallion spermatozoa. (20th November 2013) - Runcan, E. E.; Pozor, M. A.; Zambrano, G. L.; Benson, S.; Macpherson, M. L.
Summary Reasons for performing study The acrosome is a highly specialised region of the spermatozoon that is essential for fertilisation. Defects or dysfunction of this structure have been associated with fertility problems in man and various domestic species including stallions. Current methods of evaluating the acrosome of stallion spermatozoa are time consuming and require specialised equipment, which is cost prohibitive to the average practitioner. Objectives To evaluate 2 conventional stains (Dip Quick and Spermac) and determine their usefulness in assessing acrosome integrity in stallions as compared with specific acrosomal labelling with a fluorescein‐conjugated lectin – a method that has been validated for acrosome status evaluation in stallions. Study design In vivo experimental design. Methods Semen from 6 mature Miniature horse stallions of known fertility was collected on 5 separate occasions. To increase the number of reacted acrosomes, portions of each ejaculate were incubated with the calcium ionophore, A23187. Ejaculates were divided and semen samples were processed according to recommendations for fluorescein‐conjugated peanut lectin, Pisum sativum agglutin, Dip Quick, and Spermac staining methods. Slides were evaluated independently by 2 separate investigators. Spermatozoa were classified as having intact, reacting, reacted or defective acrosomes. Results All parameters obtained by both investigators, using all 3 staining methods were highly correlated (P<0.001). There was no statistical difference (P>0.05) between investigators or staining method for the percentages of intact or reacted acrosomes. However, there was a significant difference between investigators and staining methods for determining reacting acrosome percentages (P<0.05). Conclusions Dip Quick and Spermac stains are useful for determining intact vs. reacted acrosomes for stallion spermatozoa.